Psychiatric genetic counseling for patients with schizophrenia and their families - Kotzé, Carla; Zwide, Gopolang (Frontiers in Psychiatry, 2022)
Steady progress in the field of psychiatric genetics, generating new and fascinating insight into the genetic and phenotypic complexity of schizophrenia and other serious mental illnesses, have created an increased need of psychiatric genetic counseling. It is a crucial aspect of psychiatric clinical practice to ensure a balanced approach that takes into consideration genetic and environmental risk factors and ongoing education in this rapidly developing field is essential. Genetic counseling will be increasingly important to assist patients with schizophrenia and their families to make a meaningful informed decision about genetic testing. It will preempt unrealistic expectations, discrimination and stigma related to incomplete understanding of genetic test results in the psychiatric context.